Pharmacokinetics and Novel Metabolite Identification of Tartary Buckwheat Extracts in Beagle Dogs Following Co-Administration with Ethanol - Yuancai Liu; Jun Gan; Wanyu Liu; Xin Zhang; Jian Xu; Yue Wu; Yuejun Yang; Luqin Si; Gao Li; Jiangeng Huang (MDPI AG, 2019)
Alcoholic liver disease (ALD) has become a critical global public health issue worldwide. Tartary buckwheat extracts exhibit potential therapeutic effects against ALD due to its antioxidant and anti-inflammatory activities. However, in vivo pharmacokinetics and metabolite identification of tartary buckwheat extracts have not been clearly elucidated. Accordingly, the current manuscript aimed to investigate pharmacokinetics and to identify novel metabolites in beagle dogs following oral co-administration of tartary buckwheat extracts and ethanol. To support pharmacokinetic study, a simple LC-MS/MS method was developed and validated for simultaneous determination of quercetin and kaempferol in beagle dog plasma. The conjugated forms of both analytes were hydrolyzed by β-glucuronidase and sulfatase followed by liquid-liquid extraction using methyl tert-butyl ether. In addition, another effective approach was established using advanced ultrafast liquid chromatography coupled with a Q-Exactive hybrid quadrupole orbitrap high resolution mass spectrometer to identify the metabolites in beagle dog biological samples including urine, feces, and plasma. The pharmacokinetic study demonstrated that the absolute oral bioavailability for quercetin and kaempferol was determined to be 4.6% and 1.6%, respectively. Oral bioavailability of quercetin and kaempferol was limited in dogs probably due to poor absorption, significant first pass effect, and biliary elimination, etc. Using high resolution mass spectrometric analysis, a total of nine novel metabolites were identified for the first time and metabolic pathways included methylation, glucuronidation, and sulfation. In vivo pharmacokinetics and metabolite identification results provided preclinical support of co-administration of tartary buckwheat extracts and ethanol in humans.